FINITE ELEMENT COMPUTING USING NETWORK OF COMPUTERS AND PARALLEL MACHINES - Chrobak, Renata (Computer Science, 2020)
This paper presents three parallel algorithms for simulation of axisymmetrical metal forging pro- cesses. The algorithms are based on the non-overlapping domain decomposition method where a mesh of elements is divided into layers assigned to different processes. Parallel programs imp- lementing these algorithms are written in C using PVM calls. The efficiency of the parallel pro grams is verified on networked IBM RS/6000, Sun SPARCstations and HP 9000 workstations as well as on HP/Convex Exemplar SPP1000.